2013
DOI: 10.11646/zootaxa.3715.1.1
|View full text |Cite
|
Sign up to set email alerts
|

<p class="HeadingRunIn" align="left">Revision of Goniocolletes and seven Australian subgenera of Leioproctus (Hymenoptera: Apoidea: Colletidae), and description of new taxa

Abstract: This paper provides a revision of Goniocolletes Cockerell, and of Australian subgenera of Leioproctus Smith (Hymenoptera: Colletidae: Paracolletini) with three submarginal cells. Seven subgenera were revised: Leioproctus s.str., L. (Ceratocolletes) Michener, L. (Cladocerapis) Cockerell, L. (Excolletes) Michener, L. (Lamprocolletes) Smith, L. (Odontocolletes) Maynard, and L. (Protomorpha) Rayment, and seven new subgenera are herein described: L. (Alokocolletes) subgen.n., L. (Charicolletes) subgen.n., L. (Exley… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 1 publication
1
27
1
Order By: Relevance
“…However, unlike the colour characters mentioned in Maynard (2013), our specimens had orange legs, with dark coxae and trochanters. Comparison to the type specimen showed that these colour characters seem to have been switched both in the identification key (Maynard 2013, pg. 98) and species description (Maynard 2013, pg.…”
Section: Systematicscontrasting
confidence: 76%
See 4 more Smart Citations
“…However, unlike the colour characters mentioned in Maynard (2013), our specimens had orange legs, with dark coxae and trochanters. Comparison to the type specimen showed that these colour characters seem to have been switched both in the identification key (Maynard 2013, pg. 98) and species description (Maynard 2013, pg.…”
Section: Systematicscontrasting
confidence: 76%
“…A single specimen of Goniocolletes abdominalis (SAMA32-032978 / AUSBS 313-13) was collected on the same flowering Eucalyptus as where a number of other Goniocolletes males were caught. Using the key and information provided in Maynard’s (2013) revision, these other collected specimens of Goniocolletes initially keyed out to Goniocolletes comatus Maynard 2013. However, unlike the colour characters mentioned in Maynard (2013), our specimens had orange legs, with dark coxae and trochanters.…”
Section: Systematicsmentioning
confidence: 93%
See 3 more Smart Citations